Direct and Indirect Effects of Serum Uric Acid on Blood Sugar Levels in Patients with Prediabetes: A Mediation Analysis - Thunyarat Anothaisintawee; Dumrongrat Lertrattananon; Sangsulee Thamakaison; Sirimon Reutrakul; Boonsong Ongphiphadhanakul; Ammarin Thakkinstian (Journal of Diabetes Research, 2017)
Purpose. To estimate both direct and indirect effects (through obesity) of serum uric acid (SUA) on blood sugar in prediabetes patients. Methods. Prediabetes patients who came to the outpatient clinic of the Department of Family Medicine, Ramathibodi Hospital, were included in this cross-sectional study. Mediation analysis was applied to determine direct and indirect effects of SUA on glycemic parameters (fasting plasma glucose (FPG) and HbA1c) through waist circumference (WC). A mediation effect was estimated using the product-of-coefficient method with a bootstrap analysis of 1000 replications. Results. 1043 patients were eligible for this study. Every 1 mg/dl increase in SUA was associated with an increase in WC and then was significantly associated with an increase in FPG by 0.082 mg/dl (95% CI: 0.010, 0.154). SUA was directly associated with FPG with a coefficient of 0.413 (95% CI: 0.049, 0.776). For HbA1c, every one mg/dl increase in SUA was associated with an increase in HbA1c level through WC by 0.006 (95% CI: 0.003, 0.010). However, SUA was not directly associated with HbA1c. Conclusions. We found that an increase in SUA was directly and indirectly associated with increased FPG but the effect of SUA on HbA1c was shown when it was mediated through WC.